2014
DOI: 10.5539/ijef.v6n12p244
|View full text |Cite
|
Sign up to set email alerts
|

Economic Output and Government Expenditures: Applicability of Wagner’s Law in Jordan

Abstract: We examine the applicability of Wagner's Law in Jordan by testing the relationship between economic growth and governmental expenditures, then measuring the effectiveness of the output growth in reducing the governmental budget deficit, and followed by exploring the dependence of governmental expenditure on the governmental domestic revenues and foreign grants over the period 1980-2013. Following Peacock and Wiseman (1979 modeling to test for Wagner's Law, It was found that the elasticity of the real expenditu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…While this paper produces mixed results, the results are more inclined in favor of accepting Wagner's law. Likewise, the studies of Ghali (1997), Salih (2012), Al-Ghalbi (2012, Magableh et al (2014) and Abu-Eideh (2015) did find support for Wagner's law in the context of Saudi Arabia, Sudan, Iraq, Jordan and Palestine, respectively. This goes in line with what was propounded by Lamartina and Zghini (2010) regarding the idea that more support to Wagner's law is provided by countries with lower income per capita, as development government expenditures increase in an attempt to catch up with the more developed countries.…”
Section: Validity Of Wagner's Lawmentioning
confidence: 93%
See 1 more Smart Citation
“…While this paper produces mixed results, the results are more inclined in favor of accepting Wagner's law. Likewise, the studies of Ghali (1997), Salih (2012), Al-Ghalbi (2012, Magableh et al (2014) and Abu-Eideh (2015) did find support for Wagner's law in the context of Saudi Arabia, Sudan, Iraq, Jordan and Palestine, respectively. This goes in line with what was propounded by Lamartina and Zghini (2010) regarding the idea that more support to Wagner's law is provided by countries with lower income per capita, as development government expenditures increase in an attempt to catch up with the more developed countries.…”
Section: Validity Of Wagner's Lawmentioning
confidence: 93%
“…Moreover, using the error correction model, he found that the relationship between the variables in most of the law's variants was bi-directional, supporting both Wagner and the Keynesian hypothesis similarly. Magableh et al (2014) also used disaggregated data to test the validity of Wagner's law and found support for Wagner's law depicted in Peacock and Wiseman variant, for the Jordanian data in the period 1980-2013. They classified the government expenditure into real capital expenditure and real current expenditure and found that the real current expenditure exhibited greater responsiveness to changes in economic growth.…”
Section: Wagner's Law and Empirical Backgroundmentioning
confidence: 98%